Barriers and solutions: Australian Indigenous practitioners on addressing disproportionate representation of Indigenous Australian children known to statutory child protection. (September 2020) - Oates, Fiona
The rate of Indigenous child removal in Australia has been referred to as an epidemic. With numbers predicted to increase in the near to medium future exploring alternative ways to engage Indigenous children and families is critical. This article outlines the views of Indigenous practitioners collected as part of a doctoral study exploring the experiences of Aboriginal and Torres Strait Islander practitioners who undertake child protection work in Australia. Practitioner narratives were elicited by way of qualitative in-depth semi-structured interviews. The narratives of practitioners identify barriers in contemporary statutory child protection practices that may contribute to the disproportionate representation of Indigenous children in the statutory child protection system. Potential solutions offered by practitioners including cultural supervision for non-Indigenous practitioners are also outlined. The narratives of participants indicate that Indigenous practitioner-led policy, practice, training and programme design is critical to addressing the escalating rates of Indigenous child removal in Australia.